2016
DOI: 10.1210/en.2015-1852
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 Plays an Important Role in Regulating β-Cell Compensation for Insulin Resistance in Male Mice

Abstract: β-Cell compensation is an essential mechanism by which β-cells increase insulin secretion for overcoming insulin resistance to maintain euglycemia in obesity. Failure of β-cells to compensate for insulin resistance contributes to insulin insufficiency and overt diabetes. To understand the mechanism of β-cell compensation, we characterized the role of forkhead box O1 (FoxO1) in β-cell compensation in mice under physiological and pathological conditions. FoxO1 is a key transcription factor that serves as a nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 66 publications
1
46
1
Order By: Relevance
“…However, contradictory reports have called the generality of these observations into question. Mice lacking Foxo1 either in beta cells or throughout the entire pancreas show no increase in beta cell proliferation either on a chow or high-fat diet (Kobayashi et al, 2012), and mice overexpressing FoxO1 fed a high-fat diet actually showed increased beta cell proliferation (Zhang et al, 2016). These results suggest that FoxO1 might inhibit beta cell replication only when the insulin receptor is completely absent, which is a unique and rare state.…”
Section: Regulation Of Metabolism By Foxo1mentioning
confidence: 92%
“…However, contradictory reports have called the generality of these observations into question. Mice lacking Foxo1 either in beta cells or throughout the entire pancreas show no increase in beta cell proliferation either on a chow or high-fat diet (Kobayashi et al, 2012), and mice overexpressing FoxO1 fed a high-fat diet actually showed increased beta cell proliferation (Zhang et al, 2016). These results suggest that FoxO1 might inhibit beta cell replication only when the insulin receptor is completely absent, which is a unique and rare state.…”
Section: Regulation Of Metabolism By Foxo1mentioning
confidence: 92%
“…In addition, APOC3-tg islets had increased expression of Irs2 (Fig. 5H), whose function is critical for ␤-cell function and mass regulation (47,48). In contrast, no significant differences were seen in Glut2 and Gck expression in islets of high fat-fed APOC3-tg mice.…”
Section: Apoc3 In Nonalcoholic Fatty Liver Diseasementioning
confidence: 93%
“…This renders β-cells more vulnerable to oxidative stress, accounting in part for β-cell dysfunction in diabetes. In this context, Zhang and co-workers show that FoxO1 stimulates β-cell expression of Sod1, catalase (Cat) and glutathione peroxidase 1 (Gpx1), contributing to improved β-cell survival and function in the presence of oxidative stress (Zhang et al 2016). Kibbe and colleagues report that FoxO1 protects β-cells from oxidative stress by inhibiting the expression of thioredoxin-interacting protein (TXNIP), a cytosolic factor whose deregulation is associated with β-cell apoptosis (Kibbe et al 2013).…”
Section: Foxo Integration Of Oxidative Stress To Cell Survivalmentioning
confidence: 99%